Agent Control for Reconfigurable Open Kinematic Chain Manipulators. (15th October 2013) - Sluga, Janez; Zaletelj, Viktor; Žemva, Andrej
This paper presents a method for the autonomous control of differently structured open kinematic chains based on multi-agent system technology. The appropriate level of distributing local autonomy (agents) to a manipulative structure is defined, which makes it possible to dynamically change the number, type and structure of manipulative components without modifying their behavioural logic. To achieve fast reconfigurable and scalable manipulative systems, a new multi-agent method is developed for controlling the manipulator kinematics. The new method enables independent manipulator structure from the control system because of its structural and system modularity. The proposed method consists of kinematic equations for use in an agent environment, agent motion-planning algorithms, evaluation functions, agent control logic and kinematic algorithms. The results of simulations and real-world experiments demonstrate the usefulness of the approach for different non-redundant and redundant manipulation structures.